Nighttime enhancement of the amplitude of geomagnetic sudden commencements and its dependence on IMF-Bz - Araki, T.; Keika, K.; Kamei, T.; Yang, H.; Alex, S. (My University, 2006)
We present a statistical study of the diurnal variation of the occurrence frequency of geomagnetic sudden commencements (SCs) observed at Kakioka (geomagnetic latitude, θ = 27.4°). SCs with an H-component amplitude (ΔH) larger than 40 nT occur more frequently in the nighttime than the daytime, while those with smaller amplitudes (ΔH < 39 nT) occur more frequently in the daytime. Three large amplitude SCs (ΔH = 85, 117 and 145 nT at Kakioka) were analyzed in detail. All three exhibited larger amplitudes during the nighttime at all low latitudes except those near the dayside equator. A statistical study reveals that the averaged amplitudes are slightly larger in the daytime at Alibag (θ = 10.2°) but considerably larger in the nighttime at three higherlatitude Japanese stations, Kanoya (θ = 21.9°), Kakioka and Memambetsu (θ = 35.4°). Case studies of two moderate amplitude SCs which occurred at the same UT indicate that nighttime SC amplitudes at low latitudes are slightly (considerably) larger than daytime amplitudes when the interplanetary magnetic field (IMF) points northward (southward). We suggest that the diurnal variation of SC amplitudes can be explained by a combination of field aligned and resultant ionospheric currents produced during the main impulse of SCs.
Keywords: Geomagnetic sudden commencement; Diurnal variation; Amplitude; Interplanetary magnetic field; Field aligned current; Ionospheric current